Are Artificial Sweeteners A Public Health Hazard? - Bansal, Rahul (Indian Journal of Community Health, 2024)
It was a shocking news for all of us in India that a 10 year old Patiala girl Manvi died after consuming a cake on her birthday ordered from a local bakery through a food delivery app. Some media reports have blamed high level of saccharine in the cake.(1) According to another media report Health Minister of Punjab has ordered enquiry on her death. Whatever may have been the reason for this unfortunate event one thing is for sure that there is going to be a review/debate about the safety of these artificial sweeteners which are routinely added to various fast foods to enhance their taste including many soft drinks. Some of the commonly used artificial sweeteners are – aspartame, saccharine, sucralose, neotame, acesulfame-K, and stevia. Recently a news was published in Times of India - ‘Artificial Sweetener in sodas possibly carcinogenic: WHO’.(2) In this article it was written that – “World Health Organisation agency declared on Thursday that aspartame, an artificial sweetener widely used in diet drinks and low sugar foods could possibly cause cancer. The declaration by WHO agency of a cancer risk associated with aspartame reflects the first time the prominent international body has weighed in publicly on the effects of nearly ubiquitous artificial sweetener. Aspartame has been a contentious ingredient for decades.”